만성 두통에 대한 뇌청혈해독탕의 임상적 효과 - 김제영; Jae Young Kim; 이시섭; Si Sup Lee; 유정석; Jung Suk Yu; 송범용; Beom Yong Song; 김락형; Lak Hyung Kim; 육태한; Tae Han Yook (동의신경정신과학회지, 2007)
Objective : Chronic headache is the most common headache. The objective of this study is to find the clinical manifestation of chronic headache and has been carried out to investigate the effects of Noechongyolhaedok-tang on the chronic headache.Method : This observation was carried out on 73 patients with chronic headache. They were applied to Noechongyolhaedok-tang and the degree of improvement of chronic headache was evaluated by VAS. Results : 1. Distribution of study population by sex, age : male : female = 1 : 3, 30s-50s group = 81% Duration of onset : over 10years = 48% Reported site of chronic headache : the whole = 28% Clinical pain characteristics : be torn = 25% Frequency of headache : everyday = 72% Time of attack : irregular = 52% 2. In VAS scores, there were significant differences between before and after Noechongyolhaedok-tang treatment. There were no differences between before and after treatment in each sex and the duration of onset Conclusion : The effectiveness of Noechongyolhaedok-tang on the chronic headache was shown through VAS Further study is needed about Noechongyolhaedok-tang.